The Potency of Black Soldier Larvae (Hermetia illucens L.) as a Source of Protein for Livestock Feed - Ateng Supriyatna; Opik Taufik Kurrahman; Tri Cahyanto; Astri Yuliawati; Yuni Kulsum (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Black Soldier fly larvae is an insect capable to convert organic waste into body biomass. The purpose of this research was to determine the productivity, mass balance of the consumption process, and content of protein and fat of prepupa which has a potency as a livestock feed. This research used 6-day-old larvae, they were fed with cassava skin that has been smoothed with a variety of feeding doses: 12.5; 25; 50; 100; and 200 (mg / larvae / day) with ratio of feed and water 2: 1. The results showed that the feeding of 200 mg / larva / day produced the best larval growth with biomass productivity of 1.54 mg / day, residue yielded of 67.1 mg / day. The organic waste was convertion into larvae biomass. In this study, approximately consumption process scale is feed successfully converted to biomass 2.77%, metabolism 6.98%, and 90.24% residue. Protein content is 25.7%. It can be concluded that the larvae are able to convert organic waste into high protein biomass and potentially being used as a livestock feed. This research acts a model to predict mass balance of substrates for feed. The benefit of this research is the science approach used in this study that can be used as a reference by researchers and the community to determine the biomass production of an organism.